Thin layer drying of long pepper (Piper longum L.) - D Sneha, P Bhagyashree, B Vanita, (Journal of Spices and Aromatic Crops, 2013)
The effect of drying air temperatures on the drying kinetics of long pepper was investigated during 2010 using a hot-air tray dryer. In order to select the appropriate drying model, twelve mathematical drying models were fitted to the experimental data. Result indicated that the drying took place in the falling rate period. Considering the statistical criteria such as coefficient of determination (R2), Chi square (X2), sum of square error (SSE) and root mean square error (RMSE), Midilli et al. model was found to fit well to describe the drying behaviour of long pepper. Multiple regression analysis was used to find the correlation of the model coefficients with temperatures. Model coefficient equations predicted the moisture ratio (MR) well at various drying temperatures for long pepper with an R2=1 and SE=0. Effective moisture diffusivity (Deff) was observed in the range of 1.397 × 10-10 to 6.190 × 10-10 m2s-1 for the temperature range of 40° to 80°C. The overall acceptability (OA) (90%) was highest in tray drying method at 60°C air temperature and the drying time was reduced to 50% against sun drying. This study will be useful to optimize drying process parameters for commercial production of dried long pepper.